Destination Image and Tourists’ Place Dependence at Tablolong Beach - Maria Eleonora Rolina Noach; Odilia Renaningtyas Manifesty (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2026)
Tablolong Beach in Kupang Regency has high marine tourism potential but still faces limitations in terms of facilities and the quality of the physical environment, which affect the overall tourist experience. Interestingly, despite these constraints, the destination continues to attract repeat visitors, indicating the presence of place dependence, which makes it a compelling case for examining how destination image contributes to such attachment. This study aims to analyze the influence of destination image, which consists of cognitive, affective, and unique dimensions, on tourists' place dependence. A quantitative approach was employed, with data collected through questionnaires distributed to previous visitors and analyzed using multiple linear regression via SPSS version 26. Results show that cognitive, affective, and unique image each have a positive and significant impact on place dependence, with unique image emerging as the most dominant dimension. These findings indicate that destination development should be carried out through a design approach that not only focuses on improving facilities but also on strengthening spatial character, environmental comfort, and distinctive visual elements as part of place identity formation, which ultimately enhances tourists' place dependence.